Does Opioid Maintenance Therapy Decrease the Risk of Neonatal Withdrawal in Mothers with Opioid Use Disorder? [28N]. (May 2018) - Ly, Victoria; Persad, Malini D.; Herrera, Kimberly; Garry, David; Garretto, Diana
Abstract : INTRODUCTION: The objective of the study is to determine if opioid maintenance therapy decreases the risk of neonatal abstinence syndrome in pregnant women with opioid use disorder. METHODS: A retrospective cohort study of pregnant women with opioid use disorder was performed at a tertiary care hospital from January 2016 to June 2016. Women were identified using the hospital's delivery logs. Women were categorized by whether they were on opioid maintenance therapy or actively using opioids. Maternal demographics, medical history, social history, delivery characteristics and neonatal outcomes were collected. A composite adverse neonatal outcome score was created and defined as the presence of any of the following: preterm delivery, birthweight <2500 grams, Apgar score < 7 at 5 minutes, NICU admission, and neonatal abstinence syndrome. Parametric and nonparametric statistics were used to compare groups. A p value of < 0.05 was considered statistically significant. RESULTS: Of 1, 927 women who delivered, 50 women qualified for the study. There were no statistically significant differences in demographic characteristics between groups. Women on opioid maintenance therapy delivered at a statistically significant higher gestational age, had a higher neonatal birth weight and lower NICU admission rate compared to active opioid users. There were no statistically significant differences in neonatal outcomes, including neonatal abstinence syndrome, between groups. CONCLUSION: Opioid maintenance therapy use in pregnant women with opioid use disorder does not decrease incidence of NAS, but use may decrease the risk of preterm birth, low birth weight, and NICU admission.